Organizational Culture and its Impact on Organizational Citizenship Behavior - Zeyada, Mustafa (Human Resources Management Academic Research Society (HRMARS), 2018)
The concept of organizational culture has got developing attention in recent years both from researchers and practitioners. This article shows the author's view of how culture should be defined and explained if it is to be of value in the field of organizational psychology. Other concepts are reviewed, a brief history is presented, and case materials are presented to illustrate how to explain culture and how to think about culture change. The overall objective of this paper has been to highlight in the letters of the social process some of the more cultural and expressive characters of organizational life by introducing and explaining some concepts widely used in sociology and anthropology but which have not yet been blended into the theoretical literature of organizational behaviour. The substantive problem used here to provide a focus for these concepts has been how are organizational cultures created?
Keywords: 4. Education